2015
DOI: 10.18632/oncotarget.5646
|View full text |Cite
|
Sign up to set email alerts
|

ZNF32 protects against oxidative stress-induced apoptosis by modulating C1QBP transcription

Abstract: Reactive oxygen species (ROS)-driven oxidative stress has been recognized as a critical inducer of cancer cell death in response to therapeutic agents. Our previous studies have demonstrated that zinc finger protein (ZNF)32 is key to cell survival upon oxidant stimulation. However, the mechanisms by which ZNF32 mediates cell death remain unclear. Here, we show that at moderate levels of ROS, Sp1 directly binds to two GC boxes within the ZNF32 promoter to activate ZNF32 transcription. Alternatively, at cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…Our previous study identified two Sp1-response elements at the ZNF32 promoter regions −1318/−1304 and −43/−27. 35 An electrophoretic mobility shift assay (EMSA) confirmed that nuclear protein extracts from A549 cells might interact with probes containing the ZNF32 promoter-derived Sp1 binding sequences, and CIS treatment could further result in enhanced shifting (Figure 1f). In addition, Sp1 overexpression increased the formation of DNA-nucleoprotein complexes (Figure 1f).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Our previous study identified two Sp1-response elements at the ZNF32 promoter regions −1318/−1304 and −43/−27. 35 An electrophoretic mobility shift assay (EMSA) confirmed that nuclear protein extracts from A549 cells might interact with probes containing the ZNF32 promoter-derived Sp1 binding sequences, and CIS treatment could further result in enhanced shifting (Figure 1f). In addition, Sp1 overexpression increased the formation of DNA-nucleoprotein complexes (Figure 1f).…”
Section: Resultsmentioning
confidence: 86%
“…Our previous study demonstrated that Sp1 could precisely regulate the transcription of ZNF32 in response to oxidative stress. 35 Furthermore, the transcription factor Sp1 has been shown to induce the transcription of drug resistance-associated genes. 36, 37 Thus, we examined whether ZNF32 expression could be regulated by Sp1 in response to drug induction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SOD is capable of resisting and blocking the damaging effects of oxygen free radicals on cells and initiating the timely repair of damage to cells caused by free radicals (17). Oxidative stress results from the excessive production of free radicals in the body, which can affect protein expression and other regulatory and response mechanisms (18). When induced by free radical and compensated stress, the antioxidant capacity of a cell or organism can increase, during which the phenomenon of transiently increased levels of SOD may be observed (19).…”
Section: A B C D Discussionmentioning
confidence: 99%